Mengubah Sampah Organik Menjadi Eco Enzym Multifungsi: Inovasi di Kawasan Urban - Cucuk Wawan Budiyanto; Annisa Yasmin; Annona Nura Fitdaushi; Asa Qubaila Sitta Zidna Rizqia; Avona Rara Safitri; Devita Nurul Anggraeni; Kharimah Heba Farhana; Maryam Quatly Alkatiri; Yoga Yudha Perwira; Yoshan Ardhi Pratama (DEDIKASI: Community Service Reports, 2022)
The waste in urban areas was the concern in the KKN UNS Membangun. Around 80% of the total amount of waste generated is dominated by organic waste which is only seen as waste that has no economic value. Therefore, the community service activity of KKN UNS Membangun Desa Kelompok 37. Sangkrah Village was carried out in the form of socialization and training in the manufacture of eco-enzyme multipurpose liquid. Organic waste can be processed into eco enzyme which is useful as a cleaning liquid, wound treatment, and plant fertilizer. Socialization activities and training on the manufacture of eco-enzyme multipurpose liquid were carried out offline in Sangkrah Village, Pasar Kliwon District, Surakarta, Central Java, Indonesia by implementing strict health protocols. Socialization activities and training on the making of eco enzyme were attended by representatives of the residents to prevent crowds. This activity aims to make the Sangkrah Village community able to utilize organic waste so that it can be used and even can add to the economic value of the surrounding community.